Formal Concept Analysis 6th International Conference, ICFCA 2008, Montreal, Canada, February 25-28, 2008, Proceedings - Medina, Raoul; Obiedkov, Sergei (Lecture Notes in Artificial Intelligence, 2008)
Formal Concept Analysis (FCA) is a mathematical theory of concepts and c- ceptualhierarchyleadingtomethodsforconceptuallyanalyzingdataandkno- edge. The theoryitselfstronglyreliesonorderandlatticetheory,whichhasbeen studied by mathematicians over decades. FCA proved itself highly relevant in several applications from the beginning, and, over the last years, the range of applicationshaskeptgrowing. The mainreasonfor this comesfromthe fact that our modern society has turned into an "information" society. After years and years of using computers, companies realized they had stored gigantic amounts of data. Then, they realized that this data, just rough information for them, might become a real treasure if turned into knowledge. FCA is particularly well suited for this purpose. From relational data, FCA can extract implications, - pendencies, concepts and hierarchies of concepts, and thus capture part of the knowledge hidden in the data. The ICFCA conference series gathers researchers from all over the world, being the main forum to present new results in FCA and related ?elds. These results range from theoretical novelties to advances in FCA-related algorithmic issues, as well as application domains of FCA. ICFCA 2008 was in the same vein as its predecessors: high-quality papers and presentations, the place of real debate and exchange of ideas. ICFCA 2008 contributed to strengthening the links between theory and applications. The high quality of the presentations was the result of the remarkable work of the authors and the reviewers. We wish to thank the reviewers for all their valuable comments, which helped the authors to improve their presentations.